Molecular Typing of ST239-MRSA-III From Diverse Geographic Locations and the Evolution of the SCCmec III Element During Its Intercontinental Spread - Monecke, Stefan; Slickers, Peter; Gawlik, Darius; Müller, Elke; Reissig, Annett; Ruppelt-Lorz, Antje; Akpaka, Patrick E.; Bandt, Dirk; Bes, Michele; Boswihi, Samar S.; Coleman, David C.; Coombs, Geoffrey W.; et al. (Frontiers in Microbiology, 2018)
ST239-MRSA-III is probably the oldest truly pandemic MRSA strain, circulating in many countries since the 1970s. It is still frequently isolated in some parts of the world although it has been replaced by other MRSA strains in, e.g., most of Europe. Previous genotyping work (Harris et al., 2010; Castillo-Ramírez et al., 2012) suggested a split in geographically defined clades. In the present study, a collection of 184 ST239-MRSA-III isolates, mainly from countries not covered by the previous studies were characterised using two DNA microarrays (i) targeting an extensive range of typing markers, virulence and resistance genes and (ii) a SCCmec subtyping array. Thirty additional isolates underwent whole-genome sequencing (WGS) and, together with published WGS data for 215 ST239-MRSA-III isolates, were analysed using in-silico analysis for comparison with the microarray data and with special regard to variation within SCCmec elements. This permitted the assignment of isolates and sequences to 39 different SCCmec III subtypes, and to three major and several minor clades. One clade, characterised by the integration of a transposon into nsaB and by the loss of fnbB and splE was detected among isolates from Turkey, Romania and other Eastern European countries, Russia, Pakistan and (mainly Northern) China. Another clade, harbouring sasX/sesI is widespread in South-East Asia including China/Hong Kong, and surprisingly also in Trinidad & Tobago. A third, related, but sasX/sesI-negative clade occurs not only in Latin America but also in Russia and in the Middle East from where it apparently originated and from where it also was transferred to Ireland. Minor clades exist or existed in Western Europe and Greece, in Portugal, in Australia and New Zealand as well as in the Middle East. Isolates from countries where this strain is not epidemic (such as Germany) frequently are associated with foreign travel and/or hospitalisation abroad. The wide dissemination of this strain and the fact that it was able to cause a hospital-borne pandemic that lasted nearly 50 years emphasises the need for stringent infection prevention and control and admission screening.